Smoking Affects Bone Healing and Blood Perfusion - Shakeela Nazir, Fatima Qaiser, Ashiq Hussain, Asma Kazi, Aisha Aziz, Ayesha Kamran (Pakistan Journal of Medical & Health Sciences, 2022)
Nicotine is the primary component in cigarettes that is responsible for the negative effects that tobacco has on the body. Nicotine is also the primary component responsible for the addiction that can develop from smoking. Tobacco addiction is also primarily caused by nicotine, which is another component of tobacco. Aim: The effect that nicotine has on the rate at which bones can recover after being shattered is still a topic of ongoing debate. The study of bone repair and regeneration is made a great deal easier by the utilisation of a model that is known as distraction osteogenesis. The mandibular extension of a rabbit model is serving as the subject of the inquiry that is now being conducted. Duration & Place of Study: October 2018 to March 2021 Rashid Latif medical college Lahore Method: Using the rabbit as a test subject, the purpose of this study is to evaluate the influence that nicotine has on blood perfusion, angiogenesis, and bone formation. There were a total of forty rabbits, and they were distributed among the control group, which received no nicotine, and the nicotine group, which received nicotine. The bunnies were distributed to the several groups in a haphazard manner. It was discovered that each rat had been exposed to nicotine or a placebo for a total of seven weeks during the course of the experiment. After a period of consolidation time ranging from two to four weeks post osteotomy, the animals were slaughtered and their mandibles were removed. After this, there was a lag time of three days, and then there was active distraction for eleven days. Utilizing the techniques of Laser Doppler monitoring and Collagen IV immunohistochemical labelling, respectively, allowed for the assessment of both vascularization and blood perfusion. Studies that were radiographic, histological, and immunohistochemical in nature were carried out in order to investigate the development of bone. Result : According to the findings, being exposed to nicotine led to an increase in the density of microvessels, but it had a detrimental effect on the flow of blood and the development of bones. In addition to this, it was found that the expression of bone morphogenetic protein (BMP)-2 in osteoblasts was lower than it had been in the past. In the process of distraction regeneration, ischemia and a low oxygen tension were both present, and the creation of cartilage islands on a consistent basis was a sign of both of these circumstances. Result: As a result of our investigation, we got to the realisation that nicotine consumption slows down the process of bone regeneration. We hypothesise that this takes place as a result of the fact that nicotine leads to ischemia and has an effect that is directly inhibitory on osteoblastic cells. It has been demonstrated that nicotine causes an increase in angiogenesis; however, this improvement is not adequate to compensate for the harmful effect of vasoconstriction caused by nicotine.